Faktor-faktor Risiko Terjadinya Penyakit Gastritis di Rumah Sakit Umum Delia Kecamatan Selesai Kabupaten Langkat - Ilham Syahputra Siregar; Irma Handayani; Yulianti Yulianti (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
Gastritis is an inflammation of the gastric mucosa. This inflammation can result in swelling of the gastric mucosa until the detachment of the superficial mucosal epithelium, which is the most important cause of digestive tract disorders. Epithelial detachment will stimulate the onset of inflammation in the stomach. Gastritis, a term known by the public as ulcer or gastric disease. Some of the risk factors for gastritis include consuming spicy, coconut milk, and gassy foods, improper meal frequency, and frequent caffeine consumption. The purpose of this study was to determine the risk factors for gastritis disease at Delia Hospital, Selesai District, Langkat Regency in 2021. This research is descriptive with a cross sectional design conducted on 30 gastritis patients. The measuring instrument for this study used a questionnaire. The results of this study indicate that the majority of risk factors for gastritis disease in patients at Delia General Hospital, Finish District, Langkat Regency in 2021 due to food type factors, namely 14 people (46.7%).